2007 IEEE 9th Workshop on Multimedia Signal Processing 2007
DOI: 10.1109/mmsp.2007.4412808
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Social Communication in High-Functioning Children with Autism through a Co-Located Interface

Abstract: In this paper we describe a pilot study for an reality therefore making ineffective the use of this type of intervention ained at enhancing social skills in high functioning technology [7]. children with autism. We found initial evidences that the use of aIn a previous study [9], we experimented with a co-located social interaction and may lessen the repetitive behaviors typical interface where pairs of children (not affected by of autism. These positive effects also appear to be transferred to developmental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 4 publications
0
27
0
8
Order By: Relevance
“…Three pairs of children diagnosed with high-functioning autism played with this interface multiple times per week over the course of three weeks, and the researchers found that after participating in all of the play sessions, the children displayed more social behaviours such as making eye contact, positive affect while making eye contact, and sharing emotions than they did beforehand. [8]. Additionally, the children displayed fewer stereotypically "autistic" behaviours while playing with the StoryTable than they did while participating in other activities, and also spent more time playing social games, whether simple or complex, as well as less time playing in parallel with another child after participating in the study [25].…”
Section: Related Workmentioning
confidence: 93%
“…Three pairs of children diagnosed with high-functioning autism played with this interface multiple times per week over the course of three weeks, and the researchers found that after participating in all of the play sessions, the children displayed more social behaviours such as making eye contact, positive affect while making eye contact, and sharing emotions than they did beforehand. [8]. Additionally, the children displayed fewer stereotypically "autistic" behaviours while playing with the StoryTable than they did while participating in other activities, and also spent more time playing social games, whether simple or complex, as well as less time playing in parallel with another child after participating in the study [25].…”
Section: Related Workmentioning
confidence: 93%
“…Increased realism [Herrera G, 2008], [Bauminger N, 2007] would influence the degree of ecological validity achieved and subsequent degree of skill transfer. Increasing in complexity, touch-screen technology has facilitated human-computer interaction without a traditional mouse or joystick.…”
Section: B Virtual Environmentsmentioning
confidence: 99%
“…Diamond-Touch technology was integrated with the Story Table interface to allow multiple children to create an imaginative story together by selecting, combining and sequencing a series of on-screen virtual characters and events. Some story elements required 2 children to touch the screen before they were integrated into the story, reinforcing joint attention, communication and negotiation.Authors in [Bauminger N, 2007] evaluated this system with 3 dyads (a dyad is composed of 2 children with autism), aged 9-11 years old, to teach and reinforce key social skills, such as eye contact, turn-taking, sharing and joint directed behavior. During the intervention, the dyads were instructed to create and narrate stories using backgrounds and characters that were jointly chosen.…”
Section: B Virtual Environmentsmentioning
confidence: 99%
“…Dentre eles, encontram-se trabalhos naárea de interação social (Silva, 2012), robótica (Robins et al, 2005), realidade virtual (Millen et al, 2010) (Parsons and Mitchell, 2002) e comunicação (Bauminger et al, 2007) (Cunha, 2011) (Massaro and Bosseler, 2003).…”
Section: Conceituação E Declaração Do Problemaunclassified
“…Foram encontrados poucos trabalhos que tratam oâmbito da comunicação de fato, a conversação entre crianças com autismo com outras crianças, terapeutas ou pais, seja diretamente ou por meio de uma interface (uma vez que muitas das crianças com autismo são não verbais). Dentre os trabalhos que abordam este assunto, pode-se mencionar (Bauminger et al, 2007) e (Kravits et al, 2002). Porém, ambos os trabalhos foram realizados com poucas crianças (três e uma, respectivamente), o que pode ser um indício de que novas pesquisas devem ser realizadas para validar o uso de computadores no auxílio do desenvolvimento da comunicação por crianças com autismo.…”
Section: Conceituação E Declaração Do Problemaunclassified